DESAIN BAHAN AJAR E-MODUL MENULIS TEKS DEBAT BERBASIS MODEL PEMBELAJARAN SSCS BERBANTUAN APLIKASI CANVA DAN HEYZINE - Vinna Rumayara; Diena San Fauziya; Yusep Ahmadi F (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the need for innovative teaching materials for learning to write debate texts. The purpose of this study is to describe the results of the SSCS-based (Search. Solve, Create, Share) e-module design with the help of the Canva and Heyzine applications for learning to write debate  texts,  as  well  as  knowing  the feasibility of teaching materials according to the needs of students in the field. SSCS is a problem-solving-oriented learning model. Data was obtained from expert validation sheets, teacher assessment questionnaires, and student response questionnaires. The subjects of this study were two expert lecturers, one Indonesian language subject teacher, and 100 class X students as respondents. The result of the acquisition of scores in this study indicates that the e-module for writing debate texts based on SSCS with the help of the Canva and Heyzine applications received a "Very Good" assessment response with a percentage of student responses of 81.34%, expert validation of 91.77%. The product is categorized as better and suitable for use in schools if the percentage score obtained is higher, the better the level of eligibility of teaching materials.